Neural Stem Cells in Adult Mammals are not Astrocytes. (November 2022) - Velloso, Fernando Janczur; Shankar, Sandhya; Parpura, Vladimir; Rakic, Pasko; Levison, Steven W.
At the turn of the 21st century studies of the cells that resided in the adult mammalian subventricular zone (SVZ) characterized the neural stem cells (NSCs) as a subtype of astrocyte. Over the ensuing years, numerous studies have further characterized the properties of these NSCs and compared them to parenchymal astrocytes. Here we have evaluated the evidence collected to date to establish whether classifying the NSCs as astrocytes is appropriate and useful. We also performed a meta-analysis with 4 previously published datasets that used cell sorting and unbiased single-cell RNAseq to highlight the distinct gene expression profiles of adult murine NSCs and niche astrocytes. On the basis of our understanding of the properties and functions of astrocytes versus the properties and functions of NSCs, and from our comparative transcriptomic analyses we conclude that classifying the adult mammalian NSC as an astrocyte is potentially misleading. From our vantage point, it is more appropriate to refer to the cells in the adult mammalian SVZ that retain the capacity to produce new neurons and macroglia as NSCs without attaching the term "astrocyte-like."